Spinoplastic Surgery: A Review of Techniques, Indications, and Optimal Patient Selection - Daniel Vernik; Camryn Payne; Krishna Sinha; Casey Martinez; Walter Nicholas Jungbauer; Jonathan L. Jeger; Michael Bohl; Alexander E. Ropper; Sebastian Winocour; Edward Reece (Brain Sciences)
Background/Objectives: Spinoplastic surgery is an emerging multidisciplinary field developed to address and reduce the complication of pseudoarthrosis following complex spinal reconstructions. While the number of spinal fusion procedures continues to rise every year, fusion failure rates remain as high as 40%. Although pseudoarthrosis may not always manifest clinically, it remains a leading cause of persistent pain and need for subsequent revision surgeries. The multidisciplinary collaboration between spine and plastic surgeons in spinoplastic surgery has therefore emerged as a proactive strategy aimed at preventing complications, particularly in patients identified as high-risk for pseudoarthrosis. As the patient population expands and spinoplastic surgery continues to evolve, refining patient selection criteria becomes essential for achieving optimal surgical outcomes. This review aims to provide a comprehensive overview of recent advancements in spinoplastic surgery, highlighting current indications, surgical techniques, recent case reports, and strategies for identifying suitable candidates. Methods: We performed a narrative review of English language literature through April 2025. Spinoplastic case reports and case series published within the last 20 years were included in the review. Results: Indications for use of a spinoplastic approach clustered into prior fusion failure, extensive oncologic resection, severe spinal deformity, procedures requiring extensive spinal involvement, and/or patients at risk for impaired bone healing. Succesful radiographic union and improvement of symptoms were widely reported across all 9 case reports/series. Conclusions: Although evidence is presently limited, spinoplastic surgery appears to achieve high bone graft fusion rates with acceptable morbidity and functional improvement in a carefully selected group of high-risk spinal reconstruction patients. Still, larger prospective studies are warranted to refine patient selection and validate functional benefit.